Analisis Makna Kanyouku yang Menggunakan Kanji Koshi dalam Kodansha’s Dictionary of Basic Japanese Idioms - Felicia Felicia (Bina Nusantara University, 2013)
Idiom is quite interesting to discuss since it contains a lot of connotations. This study examined the meaning of kanyouku (idiom) which used koshi (eye) kanji in Kodansha’s Dictionary of Basic Japanese Idioms. The method used in this study was library research by collecting data from Kodansha’s Dictionary of Basic Japanese Idioms. The purpose of this study was to determine to what extent the use of koshi (hips) in the Japanese idiom was. After analyzing the idiom that uses koshi (hips), the research concludes that the meaning contained in the idiom was connotations.